A Study on Socio Economic Background and Status of Women Entrepreneurs in Small Scale Industries - Mathivannan, S.; Selvakumar, M. (Indian Journal of Marketing, 2008)
Women were the first humans to taste bondage. She was a slave before slavery existed. Inferiority can largely be attributed to her sexual peculiarities. Man has always played the role of a Lord; as a result his physical and mental development took place at a good pace befitting his occupation and field of interest. On the contrary, the overall growth of women remained stunted. By sheer custom even the most ignorant and worthless man has been enjoying superiority over women, which they do not deserve. Women were denied the benefit of education. They had no opportunities to develop their natural capacities and became helpless, illiterate, narrow mined and peevish. Of the world’s one billion illiterate adults, two-third is women.